Sei sulla pagina 1di 3

Practice

practice problem 1
A wooden pallet carrying a load of 600 kg rests on a
wooden floor.
a. A forklift driver decides to push it without lifting it.
What force must be applied to just get the pallet moving?
b. After a bit of time, the pallet begins to slide. How fast is the
pallet moving after sliding under the same force you
calculated in part a. for half a second?
c. If the forklift stops pushing, how far does the pallet slide
before coming to a stop?

solution

Four forces are acting on the pallet: the downward pull of


earth's gravity, the normal force of the floor pushing up, the
forward push of the forklift, and the backward resistance of
friction. Weight and normal are equal throughout this
example since the floor is level. Friction changes from static
to kinetic — static friction initially since the pallet isn't
moving initially, then kinetic friction once the pallet gets
going. The push also changes from nothing to the value
needed to get the pallet moving, then back to nothing after
0.5 seconds of motion.
a. To get the pallet started, the driver must push it with a
force equal to the maximum static friction.
P = fs = µsN = µsmg
P = (0.28)(600 kg)(9.8 m/s2)
P = 1,646 N
b. Once the pallet starts moving, the coefficient of friction
drops from its static value to its kinetic value.
fk = µkN = µkmg
fk = (0.17)(600 kg)(9.8 m/s2)
fk = 1,000 N

c. But the forklift is still pushing with 1,650 N of force.


Thus we have a nonzero net force.
∑F = P − fk
∑F = 1,646 N − 1,000 N
∑F = 646 N

d. A net force causes acceleration.


a = ∑F/m
a = (646 N)/(600 kg)
a = 1.08 m/s2

e. Acceleration goes with a change in velocity.


v = v0 + at
v = (1.08 m/s2)(0.5 s)
v = 0.54 m/s
f. Once the forklift stops pushing, kinetic friction becomes
the net force. This net force will cause an acceleration
opposite the direction of motion. When one vector is
opposite another, one of the two needs to be negative. The
convenient thing to do for this problem is to let friction be
the negative one.
a = ∑F/m = fk/m
a = (−1,000 N)/(600 kg)
a = −1.67 m/s2

g. Pick the appropriate equation of motion

h. v2 = v02 + 2a∆s

i. Eliminate the zero term (final velocity), solve for


distance, substitute, and calculate. Watch how the negative
signs disappear. This has to happen. An object moving
forward should be displaced forward.
−v02
∆s =
2a
−(0.54 m/s)2
∆s =
2(−1.67 m/s2)
∆s = 0.087 m